2020
DOI: 10.1142/s0192415x20500640
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chinese Medicine in the Management of Critical Conditions: A Review on Sepsis

Abstract: Critical care medicine is a medical specialty engaging the diagnosis and treatment of critically ill patients who have or are likely to have life-threatening organ failure. Sepsis, a life-threatening condition that arises when the body responds to infection, is currently the major cause of death in intensive care units (ICU). Although progress has been made in understanding the pathophysiology of sepsis, many drawbacks in sepsis treatment remains unresolved. For example, antimicrobial resistance, controversial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…The immune response plays an important role in disease development because severe inflammation and suppressed immunization can increase the risk of infections, multiple organ failure, or death (Sharma et al, 2015). It has been reported that many traditional Chinese herbs with the effect of promoting blood circulation and removing blood stasis could also enhance the body's immune function, which was beneficial to balance immune responses to infection (Fan et al, 2020). To confirm the effect of LHPW on immune response and exposit the molecular mechanism, we used the macrophage RAW 264.7 as induced model cells.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response plays an important role in disease development because severe inflammation and suppressed immunization can increase the risk of infections, multiple organ failure, or death (Sharma et al, 2015). It has been reported that many traditional Chinese herbs with the effect of promoting blood circulation and removing blood stasis could also enhance the body's immune function, which was beneficial to balance immune responses to infection (Fan et al, 2020). To confirm the effect of LHPW on immune response and exposit the molecular mechanism, we used the macrophage RAW 264.7 as induced model cells.…”
Section: Discussionmentioning
confidence: 99%
“…Play an anti-inflammatory effect, thereby maintaining intestinal homeostasis. In conclusion, herbal medicine can maintain the intestinal microecological balance, prevent the migration of flora, and avoid the induction of endotoxemia, which is extremely important for the prevention and treatment of sepsis ( Varon, 2009 ; Varon and Varon, 2015 ; Fan et al, 2020 ).…”
Section: Herbal Medicine Gut Microbiota and Coronavirus Disease 19mentioning
confidence: 99%
“…The ongoing COVID-19 pandemic has infected over 20,000,000 people around the world, claiming the lives of nearly 5 million people worldwide. Among the patients hospitalized with COVID-19, 26% have been treated as critical cases, which could involve sepsis or even septic shock [5]. Septic shock is a subset of sepsis in which underlying circulatory and cellular-metabolic abnormalities are profound enough to substantially increase mortality, and operationally defined as requiring vasopressor therapy to maintain a mean arterial blood pressure of >65 mmHg and an increased plasma lactate level of >2 mmol/L [1,6].…”
Section: Introductionmentioning
confidence: 99%